2019
DOI: 10.1002/ppsc.201900391
|View full text |Cite
|
Sign up to set email alerts
|

Room Temperature Synthesis of Phosphine‐Capped Lead Bromide Perovskite Nanocrystals without Coordinating Solvents

Abstract: The room temperature synthesis of perovskite nanocrystals (NCs) is typically achieved by employing a ligand-assisted reprecipitation (LARP) method, which can be handled in air, and its products are comparable to what is obtained using the traditional hot-injection method. However, the LARP method typically requires the use of coordinating polar solvents such as dimethylformamide, that are not appropriate for large-scale production due to toxicity concerns and can also degrade or form defective perovskite NCs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 45 publications
1
40
0
Order By: Relevance
“…The solution of NCs was then stored in a refrigerator for 24 h. A final centrifugation step was then used to remove the precipitate before it was used for the experiments. The synthesis of Cs-oleate and NCs follows previously published recipes 23 , 41 .…”
Section: Methodsmentioning
confidence: 99%
“…The solution of NCs was then stored in a refrigerator for 24 h. A final centrifugation step was then used to remove the precipitate before it was used for the experiments. The synthesis of Cs-oleate and NCs follows previously published recipes 23 , 41 .…”
Section: Methodsmentioning
confidence: 99%
“…In addition, it was shown that compared with a traditionally used ligand combination, phosphine ligands could be washed off easily, which would benefit the future development of optoelectronic devices. [ 52 ]…”
Section: Synthesis Of Pncsmentioning
confidence: 99%
“…Typically, short esters have been most successful. Depending on the ligand system employed, butyl acetate, [44] ethyl acetate, [35,41,43,[71][72][73][74][75][76][77] mixtures of ethyl and methyl acetate, [78,79] and methyl acetate alone, [67,[80][81][82][83] have been employed. Figure 6 shows a screening study of 36 potential antisolvents, it concurred on the efficacy of short esters, but indicated that diethylene glycol dimethyl ether (diglyme) was the most effective.…”
Section: Antisolvent Purificationmentioning
confidence: 99%